The role of community participation in intermittent preventive treatment of childhood malaria in southeastern Ghana - Kpormegbe, S.K.; Ahorlu, C.K. (Ghana Medical J, 2014)
Malaria remains a major cause of morbidity and mortality in Ghana. Very little attention was paid to community participation in malaria control in the past and this has affected most of the desired outcomes. The recent recognition of the importance of community participation in malaria control had informed the implementation of Intermittent Preventive Treatment of Childhood Malaria (IPTc). The intervention was implemented in the Shime sub-district of the Keta District in Ghana and this paper reports the evaluation of the community involvement aspect of the project.
Keywords: Intermittent Preventive Treatment of Childhood Malaria; Home Management of Malaria; Ghana; Community Participation; Acceptability